Mechanical testing of miniature carbon fiber reinforced polymer (CFRP) samples under digital light microscopy - E. S. Statnik; Iu. A. Sadykova; E. N. Prokopev; A.I. Salimon; E. V. Nazarov; N. V. Turbin; A.M. Korsunsky (Fracture and Structural Integrity)
The rapid development of inhomogeneous and anisotropic materials like carbon fiber reinforced polymers (CFRP) with epoxy matrices necessitates a multidisciplinary approach for safe use. This approach should integrate computational modeling and experimental testing across various scales, such as microscopic (1 mm), miniature (10 mm), and larger engineering samples. Mechanical testing machines must be specifically designed and optimized for each scale, combined with microscopy to observe the response under tension, bending, and compression. This setup enables real-time imaging of defect and crack initiation. Key challenges in miniature sample testing include microscope stage limitations, focusing geometry, force and displacement resolution, and fast data acquisition. The study reported here presents the customization of a 1 kN universal testing machine for in situ testing of miniature CFRP samples in combination with digital light microscopy. The observations made in the course of the present study provide valuable insight into the practical realization of miniature sample mechanical testing. Of particular note is the strain mapping capability across the sample surface afforded by the use of Digital Image Correlation